Octagonal Flower‐like CuO/C/NF Nanocomposite as a Self‐Supporting Anode for High‐Performance Lithium‐Ion Batteries. Issue 19 (12th October 2020) - Zhang, Ruili; Li, Xuehong; Ni, Liping; Xie, Anjian; Li, Panpan; Shen, Yuhua; Lao, Li
Abstract: At present, the high theoretical specific capacity CuO‐based anodes are considered as a potential host for lithium‐ion batteries (LIBs). Unfortunately, the intrinsic poor conductivity of metal oxide and the huge volume expansion during the cycling caused serve capacity fading and unsatisfactory cycling stability. Here, a porous free‐standing octagonal flower‐like copper oxide (CuO)/carbon(C)/nickel foam (NF) multilevel structure is synthesized. The design of carbon‐coated ensures excellent mechanical strength, chemical stability and conductivity of nanocomposite, which effectively prevent the collapse and corrosion of the active material during cycle. In addition, 3D interconnected structure shortened the transmission distance of electrons and Li +, improving the ability of fast charge and discharge. The CuO/C/NF electrode exhibits high performance in cycling as the anode material for LIBs. The initial charge/discharge specific capacity of the octagonal flower‐like CuO/C/NF electrode is 871.1 mA h g −1 and 916.06 mA h g −1 at 0.5 A g −1, respectively. It achieves an outstanding discharge specific capacity of 505 mA h g −1 at 2 A g −1 after 800 cycles. This work combines CuO with a conductive matrix (carbon) and a 3D porous NF, effectively enhancing the electrochemical properties of CuO, which is of certain significance to the further research. Abstract : Stand‐up powering : A porous free‐standing octagonal flower‐like copper oxide (CuO)/carbon(C)/nickel foam (NF) multilevel structure (CuO/C/NF) is synthesized and used as anode material for lithium‐ion batteries. It achieves an outstanding discharge specific capacity of 505 mA h g −1 at 2 A g −1 after 800 cycles.